Hubungan Pengetahuan Ibu Tentang Imunisasi Dasar Lengkap dengan Kepatuhan Imunisasi Balita - Nasinatul Maulidia; Ica Maulina Rifkiyatul Islami (Universitas Pahlawan Tuanku Tambusai, 2025)
Complete basic immunization is a primary preventive measure to reduce morbidity and mortality among children under five; however, immunization compliance remains uneven. Maternal knowledge is often considered an important factor in shaping immunization behavior, although its influence may vary across contexts. This study aimed to analyze the relationship between maternal knowledge of complete basic immunization and immunization compliance among children aged 0–24 months. A quantitative analytic design was employed, with primary data collected through structured instruments measuring maternal knowledge levels and children’s immunization status. Data were analyzed using appropriate inferential statistical tests to assess the association between variables. The results indicated a significant relationship between maternal knowledge level and immunization compliance, whereby mothers with higher knowledge levels tended to have children with more complete immunization status. Nevertheless, immunization compliance was not solely determined by maternal knowledge, as it was also influenced by variations in child age, immunization schedules, access to health services, and family support. This study highlights that maternal knowledge functions as an important enabling factor, but requires supportive service contexts and social environments to enhance the sustainability and effectiveness of immunization programs.